2016
DOI: 10.1017/s0954579416000183
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mental well-being during pregnancy and glucocorticoid receptor gene promoter methylation in the neonate

Abstract: Maternal mental health during pregnancy has been linked to health outcomes in progeny. Mounting evidence implicates fetal "programming" in this process, possibly via epigenetic disruption. Maternal mental health has been associated with glucocorticoid receptor methylation (nuclear receptor subfamily 3, group C, member 1 [NR3C1]) in the neonate; however, most studies have been small (n < 100) and have failed to control for multiple testing in the statistical analysis. The Barwon Infant Study is a population-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…Mina et al found sex-specific associations suggesting that infant girls might be particularly susceptible to the effects of prenatal maternal distress on placental mRNA levels of genes regulating fetal glucocorticoid exposure and placental growth [68]. Finally, data from the Barwon Infant Study ( N = 481) showed no evidence of sex dependence in associations between PNMS and cord blood NR3C1 glucocorticoid receptor gene methylation [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Mina et al found sex-specific associations suggesting that infant girls might be particularly susceptible to the effects of prenatal maternal distress on placental mRNA levels of genes regulating fetal glucocorticoid exposure and placental growth [68]. Finally, data from the Barwon Infant Study ( N = 481) showed no evidence of sex dependence in associations between PNMS and cord blood NR3C1 glucocorticoid receptor gene methylation [25]. …”
Section: Resultsmentioning
confidence: 99%
“…The twelve studies assessing NR3C1 methylation all examined exon 1 F ; one study also examined exons 1 B and 1 D (Hompes et al, ). The number of CpG sites analyzed ranged from 2 (Murgatroyd, Quinn, Sharp, Pickles, & Hill, ) to 47 sites (Mansell et al, ). Three studies used identical data on mother‐infant dyads from the Democratic Republic of Congo (Kertes et al, ; Mulligan, D'Errico, Stees, & Hughes, ; Rodney & Mulligan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Its expression levels can decrease in chronically stressed individuals, leading to desensitization to cortisol's regulatory effect on the HPA axis [43], and thus perpetuating the physiological response to chronic stress. Studies have found that maternal prenatal perceived stress [42], depression [40] and anxiety [44] were all associated with higher levels of methylation of the NR3C1 promoter in the infants. These epigenetic changes have been associated with low birth weight [42], lethargy and hypertonia [40], respectively.…”
Section: Proposed Biological Mechanisms: Epigeneticsmentioning
confidence: 99%